Translation Inhibition of the Salmonella fliC Gene by the fliC 5′ Untranslated Region, fliC Coding Sequences, and FlgM - Rosu, Valentina (American Society for Microbiology, 2006)
The 5′-untranslated region (5′UTR) of the fliC flagellin gene of Salmonella contains sequences critical for efficient fliC mRNA translation coupled to assembly. In a previous study we used targeted mutagenesis of the 5′ end of the fliC gene to isolate single base changes defective in fliC gene translation. This identified a predicted stem-loop structure, SL2, as an effector of normal fliC mRNA translation. A single base change (−38C:U) in the fliC 5′UTR resulted in a mutant that is defective in fliC mRNA translation and was chosen for this study. Motile (Mot(+)) revertants of the −38C:T mutant were isolated and characterized, yielding several unexpected results. Second-site suppressors that restored fliC translation and motility included mutations that disrupt a RNA duplex stem formed between RNA sequences in the fliC 5′UTR SL2 region (including a precise deletion of SL2) and bases early within the fliC-coding region. A stop codon mutation at position 80 of flgM also suppressed the −38C:T motility defect, while flgM mutants defective in anti-σ(28) activity had no effect on fliC translation. One remarkable mutation in the fliC 5′UTR (−15G:A) results in a translation defect by itself but, in combination with the −38C:U mutation, restores normal translation. These results suggests signals intrinsic to the fliC mRNA that have both positive and negative effects on fliC translation involving both RNA structure and interacting proteins.